Neurologic involvement in systemic autoimmune diseases - Erkan, Doruk; Levine, Steven R. (Handbook of systemic autoimmune diseases ;, 2004)
Systemic autoimmune diseases can affect both the central and peripheral nervous systems in a myriad of ways and through a heterogeneous number of mechanisms leading to many different clinical manifestations. As a result, neurological complications of these disorders can result in significant morbidity and mortality. Advances in the diagnosis, laboratory investigations, and management of these conditions has placed an increasing burden on the practicing clinician to correctly assess and treat these patients. This volume of the Handbook of the Systemic Autoimmune Diseases will help the clinician and researcher better understand the current concepts of nervous system involvement from systemic autoimmune disorders, recognize current approaches to diagnosis and treatment, current controversies, and areas that need significant research efforts. It is believed that providing this approach in a single volume will facilitate its use as a frequent resource for all those caring for or investigating these patients and their diseases. Each chapter follows a consistent outline to provide the reader with important and useful information in an easy-to-navigate manner and is also liberally referenced to provide more primary source material for further consideration. The standardized approach to each chapter will allow the reader to be able to compare and contrast more efficiently the neurological complications of the autoimmune diseases discussed.